Realization of Quality Factors of Microservices Architecture - Ashraf Bourawy, (AlQalam Journal of Medical and Applied Sciences, 2022)
Microservices architecture has gained an increasing popularity due to its beneficial characteristics and advantages. It supports building independent, loosely coupled and single-task services while keeping track of improving availability, scalability, and fault tolerance. Many research studies have been conducted to address migration from monolith to microservices and to contribute to quality of these services. In addition, most studies’ aim is to overcome challenges and issues faced by microservices development and deployment. However, there is a gap in the literature where systematic realization of quality factors related to microservices architecture is not thoroughly investigated. The aim of this study was to address and understand the quality factors of microservices-based systems. To accomplish our objective, we conducted a systematic mapping study to identify and construct a state-of-the-art study based on the retrieved relevant studies. Based on the results of the extracted data from 112 relevant studies, ten quality factors were identified and further discussed. These recognized factors are: scalability, performance, monitorability, availability, testability, reliability, security, maintainability, fault tolerance and reusability. Moreover, different challenges were identified and provided recommendations to address these issues. Although different quality factors were addressed, we concluded that more attention should be given to some factors such as security, availability, reliability, and reusability. In addition, trade-off between some factors such as scalability and performance should be addressed to optimize the overall system performance and to avoid service degradation. اكتسبت بنية الخدمات المصغرة شعبية متزايدة بسبب خصائصها ومزاياها المفيدة. فهي تدعم بناء خدمات مستقلة ومقترنة بشكل غير متماسك وذات مهمة واحدة مع تتبع تحسين التوافر وقابلية التوسع والتغلب على الأخطاء. وقد أُجريت العديد من الدراسات البحثية لمعالجة الانتقال من الخدمات الأحادية إلى الخدمات المصغرة والمساهمة في جودة هذه الخدمات. بالإضافة إلى ذلك، تهدف معظم الدراسات السابقة إلى التغلب على التحديات والمشاكل التي تواجه تطوير الخدمات المصغرة ونشرها. ومع ذلك، هناك فجوة في الأبحاث حيث لم يتم التحقيق بدقة في الإدراك المنهجي لعوامل الجودة المتعلقة ببنية الخدمات المصغرة. تهدف هذه الدراسة إلى معالجة وفهم عوامل الجودة في الأنظمة القائمة على الخدمات المصغرة. ولتحقيق هدفنا، أجرينا دراسة منهجية لتحديد وبناء دراسة حديثة بناءً على الدراسات السابقة ذات الصلة. استنادًا إلى نتائج البيانات المستخرجة من 112 دراسة ذات صلة، تم تحديد عشرة عوامل للجودة ومناقشتها بشكل أكبر. هذه العوامل التي تم التعرف عليها هي: قابلية التوسع، كفاءة الأداء، وقابلية المراقبة، والتوافر، وقابلية الاختبار، والموثوقية، والأمن، وقابلية الصيانة، والتسامح مع الأخطاء، وقابلية إعادة الاستخدام. علاوة على ذلك، تم تحديد التحديات المختلفة وتقديم توصيات لمعالجة هذه القضايا. على الرغم من تناول عوامل الجودة المختلفة، فقد خلصنا إلى أنه ينبغي إيلاء المزيد من الاهتمام لبعض العوامل مثل الأمان والتوافر والموثوقية وقابلية إعادة الاستخدام. بالإضافة إلى ذلك، ينبغي معالجة المفاضلة بين بعض العوامل مثل قابلية التوسع وكفاءة الأداء لتحسين الأداء العام للنظام وتجنب اضعاف الخدمة في الانطمة المعتمدة على بنية الخدمات المصغرة